1994
DOI: 10.1136/jcp.47.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of proliferative activity in leukaemic bone marrow using the monoclonal antibody Ki-67.

Abstract: Aims-To investigate proliferative activity in leukaemic and lymphomatous bone marrow infiltrates and to assess the feasibility of transport of specimens among institutions.Methods-Proliferative activity in bone marrow trephine cryosections from 99 patients with non-Hodgkin's lymphoma (NHL), 23 patients with acute myeloid leukaemia (AML), 11 with acute lymphoblastic leukaemia (ALL), and two with acute undifferentiated leukaemia (AUL) was investigated. Infiltration was seen in 52 out of 99 cases of NHL on bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…This time-consuming technique, which also requires isolated viable cells, has been replaced by various immunohistochemical methods that assess the proliferation rate of malignant cells (Pellegrini et al 1995). MIB-1 (which is identical to Ki-67) is a monoclonal antibody which labels a proliferation associated antigen present in the nuclei of proliferating cells in the S, G 2 , M and late G 1 phases of the cell cycle, but not in the G 0 and early G 1 phases (Gerdes et al 1984, White et al 1994. MIB-1 is a significant method for estimating the growth fraction in malignant disease and has been shown to correlate with the histopathological grade of various malignancies (Brown & Gatter 1990, Kubbutat et al 1994.…”
Section: Introductionmentioning
confidence: 99%
“…This time-consuming technique, which also requires isolated viable cells, has been replaced by various immunohistochemical methods that assess the proliferation rate of malignant cells (Pellegrini et al 1995). MIB-1 (which is identical to Ki-67) is a monoclonal antibody which labels a proliferation associated antigen present in the nuclei of proliferating cells in the S, G 2 , M and late G 1 phases of the cell cycle, but not in the G 0 and early G 1 phases (Gerdes et al 1984, White et al 1994. MIB-1 is a significant method for estimating the growth fraction in malignant disease and has been shown to correlate with the histopathological grade of various malignancies (Brown & Gatter 1990, Kubbutat et al 1994.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive cell proliferation is a characteristic of all leukemic cells. However, previous studies [ 36 , 37 ] have shown that the proliferative index of ALL cells is significantly higher compared to AML cells.…”
Section: Resultsmentioning
confidence: 92%
“…O Ki-67 é um marcador localizado no núcleo celular e é bastante utilizado para identificar células em proliferação celular, sendo este um anticorpo monoclonal (WHITE, SMITH, SMITH, 1994).…”
Section: Ki 67unclassified